Influence of polarization direction, incidence angle, and geometry on near-field enhancement in two-layered gold nanowires - 吴大建 蒋书敏 刘晓峻 (Chinese physics B, 2012)
The influences of polarization direction, incidence angle, and geometry on near-field enhancements in two-layered gold nanowires （TGNWs） have been investigated by using the vector wave function method. When the polarization direction is perpendicular to the incidence plane, the local field factor （LFF） in TGNW decreases first and then increases with the increase in the incidence angle. The minimum LFF is observed at an incidence angle of 41°. It is found that the increase in the dielectric constant of the inner core leads to a decrease in the LFF. With the increase in the inner core radius, the LFF in TGNW increases first and then decreases, and the maximum LFF is observed at an inner core radius of 27 nm. On the other hand, when the polarization direction is parallel to the incidence plane, the collective motions of the induced electrons are enhanced gradually with the decrease in the incidence angle, and hence the near-field enhancement is increased.